Analysis of Physicochemical Properties of the Turag River Water, Tongi, Gazipur in Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
The study deals with the assessment of water quality parameters including pH, DO, BOD, temperature, TDS, EC, transparency, hardness, and alkalinity of the Turag River in Tongi, Gazipur, Bangladesh. The physicochemical parameters of water were investigated for 3 points in the Turag River through experimental methods. The river water was black in color and the odor was bad which indicate that the water is polluted and dangerous for aquatic ecosystem and human health. The temperature of water was within an average value of 28.39oC which indicates standard temperature (20 to 30oC) for aquatic medium. The average value of pH was 6.83, which indicates that the value was within the standard limits (6.5 to 8.0) for aquatic organisms. The values of DO water were within the range of 0.6 to 3.9 ppm with an average value of 2.25 ppm indicating low DO value from standard level (4.0 to 6.0 ppm for domestic and 5.0 ppm for fish culture). The values of BOD were within the average value of 1.15 ppm indicating lower condition compared to standard value of BOD (6.0 ppm for fish culture and 10.0 ppm for irrigation). The average value of TDS was 340.86 ppm which indicates low TDS condition. The EC values were ranged from 35 to150 ?S/cm with an average value of 56.30 ?S/cm which indicates lower condition than the standard value. The average value of transparency was 28.39 cm. The average value of hardness was 106.79 ppm which indicates near to the standard level. The average alkalinity was 237.66 ppm indicating very lower condition than the standard limit (2000 ppm for irrigation). From this investigation, it is recommended that the water quality of the Turag River is beyond the acceptable limit. So, effective measures should be taken to reduce the level of pollution and mitigate the existing aquatic environmental problems of the Turag River.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22140 J. Environ. Sci. & Natural Resources, 7(1): 27-33 2014